2011
DOI: 10.1007/s11269-011-9942-7
|View full text |Cite
|
Sign up to set email alerts
|

Towards Quantification of the Water Footprint of Paper: A First Estimate of its Consumptive Component

Abstract: For a hardcopy of this article, printed in the Netherlands, an estimated 100 l of water have been used. Most of the water is required in the forestry stage, due to evapotranspiration (green and blue water). In addition, the water footprint during the industrial stage, as accounted for in this study, consists of evaporation from water obtained from ground water and surface water (blue water). In this study estimates are made of water requirements for producing paper using different types of wood and in differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
50
1
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(56 citation statements)
references
References 19 publications
0
50
1
5
Order By: Relevance
“…Para isso foram utilizados os resultados já publicados sobre PH na produção de papel que identificou o valor da PH verde da produção de madeira para celulose em várias partes do mundo (Van Oel e Hoekstra, 2012 . Neste estudo não foi considerada a PH cinza do cultivo da madeira.…”
Section: 2unclassified
See 2 more Smart Citations
“…Para isso foram utilizados os resultados já publicados sobre PH na produção de papel que identificou o valor da PH verde da produção de madeira para celulose em várias partes do mundo (Van Oel e Hoekstra, 2012 . Neste estudo não foi considerada a PH cinza do cultivo da madeira.…”
Section: 2unclassified
“…Os estudos têm destacado a incompatibilidade entre a disponibilidade hídrica e a demanda de água (Hoekstra et al, 2012). As métricas são fundamentais para avaliar o desempenho das atividades agropecuárias e relevantes para orientar produtores e consumidores em suas decisões.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Regarding India, the mean annual inter-state VW trade in crops is 106,000 million m 3 for the years 1997-2001 (Verma et al 2009), while China's northern and southern parts have been found to be a net virtual water exporter [having a value of 4225.4 million m 3 (year 1997)] and net virtual water importer [having a value of 148.1 million m 3 (year 1997)], respectively (Guan and Hubacek 2007). There have also been efforts to estimate the WFs of products, cities, countries, regions, and processes (Van Oel and Hoekstra 2012;Mekonnen and Hoekstra 2012a, b;Ercin et al 2012;Gerbens-Leenes and Hoekstra 2012;Jefferies et al 2012;Ruini et al 2013;Zhang et al 2011;Chapagain and Hoekstra 2011;Dong et al 2013;Vanham and Bidoglio 2013;Van Oel et al 2009;Niccolucci et al 2011). For example, Chapagain and Hoekstra (2011) However, published reports are not available on the net VW export through the trade of potash, fertilizers, crude oil, refined petroleum, olive oil, and pig iron to the 28 countries of the European Union (EU28) (2016), especially from the MENA region.…”
Section: Introductionmentioning
confidence: 99%
“…www.mdpi.com/journal/sustainability Sustainability 2015, 7,[16532][16533][16534][16535][16536][16537][16538][16539][16540][16541][16542][16543][16544][16545][16546][16547] Chico et al [21], Herath et al [22], Ene et al [23], who extended water footprint assessment to wider application for products, such as soy milk and soy burgers, sweeteners and bio-ethanol, paper, livestock, jeans and wines. Mekonnen and Hoekstra [24] measured the water footprint of crops and derived crop products in the period of 1996-2005.…”
Section: Introductionmentioning
confidence: 99%